Overview of hepatitis B virus mutations and their implications in the management of infection - Caligiuri, Patrizia (World journal of gastroenterology : WJG, 2016)
Hepatitis B virus (HBV) affects approximately two billion people worldwide and more than 240 million people in the world are currently chronic carrier that could develop serious complications in the future, like liver cirrhosis and hepatocellular carcinoma. Although an extended HBV immunization program is being carried out since the early '80s, representing effective preventive measure, leading to a dramatic reduction of HBV hepatitis incidence, globally HBV infection still represents a major public health problem. The HBV virus is a DNA virus belongs to the Hepadnaviridae family. The HBV-DNA is a circular, partial double strand genome. All coding information is on the minus DNA strand and it is organized into four open reading frames. Despite hepatitis B virus is a DNA virus, it has a high mutation rate due to its replicative strategy, that leads to the production of many non-identical variants at each cycle of replication. In fact, it contains a polymerase without the proofreading activity, and uses an RNA intermediate (pgRNA) during its replication, so error frequencies are comparable to those seen in retroviruses and other RNA viruses rather than in more stable DNA viruses. Due to the low fidelity of the polymerase, the high replication rate and the overlapping reading frames, mutations occur throughout the genome and they have been identified both in the structural and not structural gene. The arise of mutations being to develop of a whole of viral variants called "quasi-species" and the prevalent population, which favors virus replication, was selected by viral fitness, host's immune pressure and external pressure, i.e., vaccination or antiviral therapy. Naturally occurring mutations were found both in acute and chronic subjects. In the present review we examine and discuss the most recent available data about HBV genetic variability and its significance.